A novel strategy to discover and use climate-adapted germplasm - Vernooy, Ronnie; Otieno, G.; Bessette, Guy; Fadda, Carlo; Galluzzi, G.; Gevel, Jeske M.J, van de; Halewood, Michael; López Noriega, Isabel; Mathur, P.N.; Mittra, S.; Rudebjer, P.G.; Steinke, J.; et al. (Bioversity International, 2015)
Between 2012 and 2015, 150 researchers, research managers, gene bank managers, extension agents, university professors and staff of non-government organizations from Bhutan, Burkina Faso, Costa Rica, Côte d’Ivoire, Guatemala, Nepal, Rwanda, Uganda, Zambia and Zimbabwe acquired new knowledge and skills about the use of climate and crop modelling tools and data sources including the climate analogue tool introduced through the CGIAR research programme on Climate Change, Agriculture and Food Security (CCAFS). Applying these tools and data to their national context, they assessed the changing needs for national and foreign-sourced plant genetic resources for food and agriculture in the context of climate change adaptation. Research teams are now designing strategies to deploy germplasm that is better adapted to future climate changes and that could contribute to increased food security. They are integrating these strategies into organizational agenda’s that will be implemented with own resources.